First Double Cascade Tau Neutrino Candidates in IceCube and a New Measurement of the Flavor Composition - Stachurska, Juliana (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2019)
36th International Cosmic Ray Conference, Madison, Wisconsin, USA, 24 Jul 2019 - 1 Aug 2019; PoS 1015 (2019). : The IceCube Neutrino Observatory at the South Pole, which detects Cherenkov light from charged particles produced in neutrino interactions, firmly established the existence of an astrophysical high-energy neutrino component. The expected neutrino flavor composition on Earth is $\nu_e:\nu_{\mu}:\nu_{\tau}$ of about 1:1:1 for neutrinos produced in astrophysical sources through pion decay. A measurement of the flavor composition on Earth can provide important constraints on sources and production mechanisms within the standard model, and can also constrain various beyond-standard-model processes. Here the measurement of the flavor composition performed on IceCube's High-Energy Starting Events sample with a livetime of about 7.5 years is presented. IceCube is directly sensitive to each neutrino flavor via the single cascade, track and double cascade event topologies. In IceCube, $\nu_{\tau}$-CC interactions above $\sim$ 100 TeV can produce resolvable double cascades, breaking the degeneracy between $\nu_e$ and $\nu_{\tau}$ present at lower energies. IceCube's first two identified double cascades are presented and the properties of the two $\nu_{\tau}$ candidates are discussed.